Pengenalan Digital Marketing E-Katalog bagi UMKM Binaan Jakpreneur - Siti Mariam; Abdul Haeba Ramli (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of community service is to introduce e-catalog digital marketing to MSME players in DKI Jakarta Province. Jakpreneur-assisted MSME actors in DKI Jakarta Province are partners in this community service. The main problems faced by partners are the limited knowledge and skills of partners in utilizing digital marketing, partners do not have good quality product photos and partners do not have product catalogs. The solutions offered to partners are assistance in understanding the right digital marketing and making product catalogs including product data collection, product photos and product descriptions and understanding the benefits of updating product type information, photos and prices. The target to be achieved from this PKM implementation activity is the understanding of partners in the creation and use of digital marketing. Increase business through the use of advertising in digital marketing; facebook shop, facebook ads, instagram ads, google ads, e-brochures, and e-catalogs. With the digital marketing system, partners can do long-term marketing easily and quickly and can reach a wider market. The implementation of community service activities is carried out using the tutorial method, where partners get direct assistance in introducing the use and making of digital marketing. Partners are divided into several groups. This was followed by a question and answer discussion and evaluation and monitoring. Based on the results of the activity, partners were very enthusiastic as long as they followed the digital marketing e-catalog mentoring tutorial. Several questions were given by partners and partners following suggestions by utilizing the existing market place in addition to the use of social media in marketing their products.